Plastic waste processing assistance at waste banks as an effort to overcome plastic waste problems in Krukut Village, Depok City - Budhi Martana; Sigit Pradana; Sri Sulasminingsih (Universitas Muhammadiyah Magelang, 2022)
Plastic waste pollution is an issue not only on land, but also at sea. It takes 20 to 500 years for the plastic garbage produced to decompose fully. The aim of this community engagement program is to assist partners in dealing with the problem of plastic waste. Socialization, use of appropriate technology for processing plastic waste, help, and assessment are the stages of action in the implementation of this community partnership program. The program's outcomes include partners being able to use a plastic waste crusher machine to turn plastic waste into plastic pellets, that may be sold or processed into other goods, as well as a solution for reducing plastic waste generation.